In vitro antimicrobial activity of musk lime, key lime and lemon extracts against food related pathogenic and spoilage bacteria - Velu, Selvi; Abu Bakar, Fatimah; Mahyudin, Nor Ainy; Saari, Nazamid; Zaman, Muhammad Zukhrufuz (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2014)
The demand for novel antimicrobial agents from natural resources has been increased worldwide for food conservation purpose. In this study antimicrobial activity of musk lime, key lime and lemon were evaluated against various food borne pathogens and spoilage bacteria using disc diffusion test. Type of extraction solvent and concentration level significantly influenced the antibacterial activity of all the extracts. Ethanol extracts of musk lime, key lime and lemon exhibited significant broadest inhibitory activity at 100% concentration level (pure extract) compared to water and juice extracts. 100% ethanol extracts of musk lime (39.7 mm), key lime (26.7 mm) and lemon (32.0 mm) exhibited the largest diameter of inhibition zone (DIZ) against Aeromonas veronii. 100% water extracts of musk lime (25.3 mm), key lime juice extract (23.3 mm) and water extracts of lemon (23.7 mm) was most effective against food spoilage bacteria, A. veronii. The prominent results of the antimicrobial activity from lime, key lime and lemon extracts may attribute them as potential natural food preservatives and could be used in pharmaceuticals field.